Odnowa terenów zieleni w Miniprogramach Rewitalizacji Dzielnic Warszawy = Green areas renewal in Miprogrames of Warsaw District Revitalization - Domanowska, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Accessing Poland to the European Union opened new possibilities for polish cities to partly finance city development. One of the programs which enables city development financing is program URBAN II (for cities more over 20 000 inhabitants), which trough the Integrated Regional Development Programme (ZPORR- one of seven operating programs which goals refers to the implementation of European Commission on National Development Plan 2004-2006), specified rules of elaborating Local Revitalization Programs. Local Revitalization Programs contain projects of revitalization of most degraded city areas.
Keywords: Miniprogramy Rewitalizacji Dzielnic Warszawy; tereny zieleni; odnowa terenów zieleni Warszawy; Miniprogrames of Warsaw District Revitalization; green areas; green areas renew